2020
DOI: 10.1371/journal.pone.0238737
|View full text |Cite
|
Sign up to set email alerts
|

Validation and quality measurements for STS, EuroSCORE II and a regional risk model in Brazilian patients

Abstract: The objectives of this study were to describe a novel statewide registry for cardiac surgery in Brazil (REPLICCAR), to compare a regional risk model (SPScore) with EuroSCORE II and STS, and to understand where quality improvement and safety initiatives can be implemented. Methods A total of 11 sites in the state of São Paulo, Brazil, formed an online registry platform to capture information on risk factors and outcomes after cardiac surgery procedures for all consecutive patients. EuroSCORE II and STS values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
(30 reference statements)
2
4
0
4
Order By: Relevance
“…Compared to low weight or small for gestational age, the severity of lesions, and the complexity of surgical procedures were more widely accepted as significant predictors of early mortality after cardiac surgery in neonates. We found that clinical outcomes in this report were similar to those identified by the Society of Thoracic Surgeons in that the in-hospital mortality increased with higher STAT categories and Category 5 was associated with the highest risk ( 11 14 , 23 ). Additionally, a longer aortic cross-clamp time was considered an important risk factor for in-hospital mortality.…”
Section: Discussionsupporting
confidence: 82%
“…Compared to low weight or small for gestational age, the severity of lesions, and the complexity of surgical procedures were more widely accepted as significant predictors of early mortality after cardiac surgery in neonates. We found that clinical outcomes in this report were similar to those identified by the Society of Thoracic Surgeons in that the in-hospital mortality increased with higher STAT categories and Category 5 was associated with the highest risk ( 11 14 , 23 ). Additionally, a longer aortic cross-clamp time was considered an important risk factor for in-hospital mortality.…”
Section: Discussionsupporting
confidence: 82%
“…This result was in contradiction with what has been observed, during the same period, when applying these two scores in developed countries [ 14 ]. Furthermore, in a more recent cohort of 5,222 Brazilian patients, including 60% of patients who benefited from a CABG, the regional score outperformed the STS-PROM and the EuroSCORE II, which also greatly underestimated the observed mortality [ 15 ]. The calibration curves of the Euro-SCORE II and STS-PROM of this Brazilian cohort are in perfect adequacy with those generated by our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since international scores are not applicable in all countries, some national scores have emerged, and were validated on their respective populations, such as the Chinese [ 12 ], or the Australian System for Cardiac Operative Risk Evaluation [ 21 ] or the São Paulo risk Score for Brazil [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…No estado de São Paulo temos o SPScore, um índice de risco criado com inteligência artificial e que poderia ajudar para um ressarcimento mais apropriado perante as fontes pagadoras, no nosso cenário. 24 Podemos dizer que no Brasil, para acompanhar estas mudanças, existe no Departamento de Cardiopneumologia da Faculdade de Medicina da Universidade de São Paulo uma linha de pesquisa que começou em 2012 com o objetivo de estratificar e melhorar resultados em pacientes encaminhados para cirurgia cardiovascular. Alunos de graduação e pósgraduação pesquisam e publicam temas sobre implementação de grandes bancos de dados, construção de escores de risco utilizando inteligência artificial, identificação de estratégias custo-efetivas em grupos de risco e otimização de processos, entre outras.…”
Section: Lily Tomlinunclassified